Cover Image, Volume 94, Number 5, May 2022. Issue 5 (17th March 2022) - Li, Tao; Cui, Zhimin; Jia, Yunfei; Liang, Ziteng; Nie, Jianhui; Zhang, Li; Wang, Meng; Li, Qianqian; Wu, Jiajing; Xu, Nan; Liu, Shuo; Li, Xueli; et al.
Abstract : Front Cover Caption : The cover image is based on the Research Article Aggregation of high‐frequency RBD mutations of SARS‐CoV‐2 with three VOCs did not cause significant antigenic drift by Tao Li et al., https://doi.org/10.1002/jmv.27596 .